2020
DOI: 10.1371/journal.pone.0237889
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of tenascin-C inhibits breast cancer cells development by cell growth, migration, and adhesion impairment

Abstract: Tenascin-C (TNC) is an extracellular matrix (ECM) glycoprotein that plays an important role in cell proliferation, migration, and tumour invasion in various cancers. TNC is one of the main protein overexpressed in breast cancer, indicating a role for this ECM molecule in cancer pathology. In this study we have evaluated the TNC loss-off-function in breast cancer cells. In our approach, we used dsRNA sharing sequence homology with TNC mRNA, called ATN-RNA. We present the data showing the effects of ATN-RNA in M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 65 publications
0
15
0
Order By: Relevance
“…TN-C is large (~ 300 kDa) as an intact monomer and ~ 1800 kDa when assembled as a hexamer [ 15 ]. Following initial identification in gliomas in 1980 s[ 16 ], TN-C has since been found to be expressed in head and neck squamous cell carcinoma, breast [ 17 ], prostate [ 18 ], thyroid [ 19 ], pancreatic [ 20 ] cancers, melanoma [ 21 ], gastric cancer [ 22 ] and osteosarcoma [ 23 ]. In the majority of these cancers, TN-C is considered to act as a tumor promoter and is associated with a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…TN-C is large (~ 300 kDa) as an intact monomer and ~ 1800 kDa when assembled as a hexamer [ 15 ]. Following initial identification in gliomas in 1980 s[ 16 ], TN-C has since been found to be expressed in head and neck squamous cell carcinoma, breast [ 17 ], prostate [ 18 ], thyroid [ 19 ], pancreatic [ 20 ] cancers, melanoma [ 21 ], gastric cancer [ 22 ] and osteosarcoma [ 23 ]. In the majority of these cancers, TN-C is considered to act as a tumor promoter and is associated with a worse prognosis.…”
Section: Introductionmentioning
confidence: 99%
“…Tenascin C (TNC) is an extracellular matrix (ECM) glycoprotein that is overexpressed during organogenesis, particularly in the development of the central nervous system, in migration of neural crest cells, and epithelial–mesenchymal transition (EMT), but its distributions typically remain limited in adult tissues . However, increased deposition of TNC has been noticed in different types of malignancies, for instance, melanoma, bladder, breast, uterus (both the cervix and body), lung, tongue, colon, stomach, larynx, skin, and urinary tract cancer. , The elevated expression of TNC has also been observed in high-grade gliomas that positively correlates with the invasiveness of glioma cells and is suspected to be a potential biomarker of earlier detection of GBM and GSC considered as a better therapeutic target of glioblastoma. , TNC promotes tumor progression by triggering cell proliferation and differentiation, migration, and angiogenesis and participates in the development of CSC through the HH signaling pathway …”
Section: Resultsmentioning
confidence: 99%
“…Previously data demonstrated that TNC promotes several procedures in tumor progression and involved in a wide range of cellular processes including cell proliferation, migration, invasiveness, angiogenesis, and immunomodulation. [ 7 14 ] TNC is one of the most highly expressed proteins in the tumor ECM which has poor prognostic value for patient survival in a variety of malignant tumors.…”
Section: Discussionmentioning
confidence: 99%